PENGARUH MEDIA PEMBELAJARAN VIDEO TUTORIAL MYOB DAN KEMANDIRIAN BELAJAR TERHADAP HASIL BELAJAR AKUNTANSI KOMPUTER KELAS XI SMK NEGERI 1 RANGKASBITUNG - Otong Hidayat (Progress: Jurnal Pendidikan, Akuntansi dan Keuangan, 2021)
This study aims to knowing the difference between computer accounting learning outcomes of students who learn to used MYOB video tutorials and students who learn to used power point And the difference between learning outcomes of students who have high learning independence and low independence. In addition, this research aims to determine the effect of video tutorial interactions and learning independence. The results show that there is a difference in learning outcomes of 12.35% who learn used video tutorials and those who learn using power point. In addition, there is a difference in learning outcomes of 7.63%, students who have high learning independence and students who have low learning independence and there is an influence of video tutorial interactions and learning independence.